Ketimpangan Akses dan Kualitas Pendidikan Dasar di Daerah Terpencil: Analisis APS, APK, dan APM terhadap Infrastruktur, Distribusi Guru, dan Reformasi Pengajaran - Setiawati, Yuli; Fauzi, Wildan Nuril Ahmad (Musamus Journal of Primary Education, 2024)
Inequality in access and quality of basic education in remote areas is still a serious challenge, especially in areas with difficult geographical conditions such as Merauke Regency. This study aims to evaluate the gap in school infrastructure, the distribution of teaching staff, and pedagogical reform in the context of limited resources. The method used was a descriptive statistical analysis of secondary data from the Central Statistics Agency of Merauke Regency, including the School Participation Rate, Gross Participation Rate, and Pure Participation Rate, as well as the teacher-student ratio to identify inequality in access and quality of education. The results of the study show that school access is still limited for people in remote areas due to limited infrastructure and long distances, while the deficit of teaching staff has an impact on the high teacher-student ratio, hindering learning effectiveness. The lack of pedagogical adaptation to local limitations also exacerbates the educational gap. Therefore, an evidence-based policy strategy is needed that includes incentive schemes for educators, strengthening community-based schools, and reforming more adaptive learning methods to create a more inclusive and sustainable basic education system.